Preparation of Hyaluronic Acid Oligosaccharides by Enzymatic Method and Its Transdermal Absorption Activity - Huining LI; Jingliang ZHANG; Gen YANG; Xiaolu JIANG (Shipin gongye ke-ji, 2022)
To investigate the transdermal absorption activity of hyaluronic acid oligosaccharides, hyaluronic acid oligosaccharides were prepared by enzymatic degradation of hyaluronic acid using hyaluronic acid lyase, and the hyaluronic acid oligosaccharides were analyzed by infrared spectroscopy and mass spectrometry, and their hygroscopic properties, body surface moisturizing properties and transdermal absorption properties were evaluated. The results showed that the optimum substrate concentration for the enzymatic preparation of hyaluronan oligosaccharides by hyaluronan lysis enzyme was 1%, and the optimum enzyme addition was 3.0 U/mg. The enzymatic preparation of hyaluronan oligosaccharides was free of moieties, and the enzymatic products were mainly unsaturated hyaluronan disaccharides. The enzymatically prepared hyaluronan oligosaccharide had excellent surface moisturizing and transdermal absorption properties, and would have a broad application prospect in the field of biochemicals.